If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(f + -9) = -18 Reorder the terms: 2(-9 + f) = -18 (-9 * 2 + f * 2) = -18 (-18 + 2f) = -18 Add '18' to each side of the equation. -18 + 18 + 2f = -18 + 18 Combine like terms: -18 + 18 = 0 0 + 2f = -18 + 18 2f = -18 + 18 Combine like terms: -18 + 18 = 0 2f = 0 Solving 2f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '2'. f = 0 Simplifying f = 0
| (15-2s)(15-2s)= | | 3a+5a+7= | | 2a^3-18a^2-4=0 | | -10(s+2)=52 | | Log(x-15)+2=-logx | | -10(s+1)=-34 | | 4(t+5)=8# | | 52+7+Z=-8 | | 18+3t-7=51 | | 10x^4-103x^3-207x+294x^2-54=0 | | Ln(20/x) | | 3(3s+2)=33 | | 8(4s+7)=472 | | 3(3s+2)=30 | | 1/2(y-8)=2 | | 8(2l+3)=40 | | 2(2l+9)=58 | | -3(2t+1)=-27 | | 2x-22=4x+14 | | 7.5+2.5= | | 14+(29*x)=-131 | | 4(a-7)=64 | | 5(f-10)=-15 | | 5(a-8)=80 | | (u-6)*8=40 | | -102x+18=0 | | (2X+5)(X+2)=210 | | 2(2l+9)=80 | | -8(s+1)=36 | | (q-5)*2=16 | | 11x-6y=19 | | (u-4)*10=20 |